Chapter Luoghi e memorialistica. Aspetti didattici del Memoriale degli italiani di Auschwitz tra passato e presente - Bravi, Luca (Public History of Education. Teorie, esperienze, strumenti, 2022)
The Memorial for the Italian died in nazi camps is an artistic masterpiece commissioned in 1979 by the National Association Former Prisoneers in nazi camp. It was inagurated in 1980 in the National Auschwitz Museum as permanent Italian exhibition. In 2008, the museum board launched a complain about the italian exhibition: its complexion was full of echoes about the Italian Resistance. Hence, it was judged ununderstandable but also politically dangerous as Poland changed regime after 1989. In 2011, the Museum closed the italian exhibition and the National Association moved it in Florence. The paper describe how the exhibition was opened and how it worked as a tool for present time.